Difficulties in the diagnosis and management of hyponatremia - MOCAN, MIHAELA (Clujul Med, 2016)
Hyponatremia is the most common electrolyte imbalance encountered in clinical practice. Beside the difficulty of the etiological diagnosis, the general lack of awareness regarding the negative impact of hyponatremia on the quality of life and the lack of targeted treatments until recent years may be responsible for the poor management of the disorder. Therefore we consider of utmost importance to improve the knowledge regarding the diagnosis and management of hyponatremia, by underlining the difficulties of the etiological diagnosis and its management. In this respect, a short and updated literature review, with a critical appraisal of the latest guidelines will provide detailed information on how to systematically evaluate and treat the hyponatremic patients.